2017
DOI: 10.5539/jedp.v7n1p218
|View full text |Cite
|
Sign up to set email alerts
|

Accurate Diagnosis of the Syndrome in Children with Autism Spectrum Disorders and Parents’ Resilience

Abstract: Autism is considered to be a much more serious syndrome than other developmental disorders and according to studies it affects the resilience of the parents with an autistic child to a larger degree, comparatively. In this article the results of the investigation between the family resilience of the parents and their child's diagnosis of the syndrome are presented, as it was regarded that, taking into consideration the autism syndrome and Asperger syndrome, the difficulties in a row of levels would be particul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“… 12 As well as it has been reported that caregivers of a child with ASD receive much less social support than families with typically developing child. 13 …”
Section: Discussionmentioning
confidence: 99%
“… 12 As well as it has been reported that caregivers of a child with ASD receive much less social support than families with typically developing child. 13 …”
Section: Discussionmentioning
confidence: 99%
“…In this study, it was observed that families with children with autism need more psychological support than families with a child of normal development, and their anxiety levels are high and their level of relational resilience is low, education and income differences do not differ in this context. Furthermore, Kavaliotis (2017) stated that autism is a much more serious syndrome than other disabilities and examined the resilience of parents with children with autism and emphasized the importance of social support. Social support is defined as the material and spiritual help provided by the individual in the environment facing a difficult situation.…”
Section: Introductionmentioning
confidence: 99%